Hubungan Antara Penyakit Skabies Dengan Tingkat Kualitas Hidup Santri Di Pondok Pesantren Al-Muayyad Surakarta - PURWANTO, NAUFAL FARUQ (2016)
ABSTRACT RELATIONSHIP BETWEEN SCABIES DISEASE WITH QUALITY OF LIFE LEVEL SANTRI IN PONDOK PESANTREN AL-MUAYYAD SURAKARTA Naufal Faruq Purwanto¹, Ratih Pramuningtyas², Devi Usdiana Rosyidah² Fakultas Kedokteran Universitas Muhammadiyah Surakarta Goal: This research have a goal to understand the correlation between scabies disease with level quality of life santri in Pondok Pesantren Al-Muayyad Surakarta. Methods: Observational analytic with approachment cross sectional. Total sample of this research as many as 74 santris, with 31 santri suffered scabies and 43 santris unsuffered scabies. Technic sampling with simple random sampling technic. The research do at Pondok Pesantren Al-Muayyad Surakarta on November 2015. The data analyzed by Kolmogorov-Smirnov test with SPSS program. Result: The research showing the biggest of total sample there is suffered scabies are man, 26 santri and the biggest group of age is 14-16 years old. Santri who's suffered scabies with disruption quality of life have a number 10 santri, just enough quality of life is 9 santri, few disruption quality of life is 7 santri, and without disruption quality of life is 5 santri. Santri who's unsuffered scabies with a few disruption quality of life have a number 15 santri and without disruption quality of life 28 santri. The result showed value p=0,000 (p<0,05) and showing there is correlation between of two variables who tested. Conclusion: The conclusion of this research is have correlation between scabies disease with level quality of life santri based on disruption of symptoms, pleasure and shy, social correlation, managing home, physical exercise, and study or work. 1Student of medical faculty Muhammadiyah Surakarta University 2Lecture of medical faculty Muhammadiyah Surakarta University